The lithium isotopic composition of orogenic eclogites and deep subducted slabs - Marschall, H; Pogge von Strandmann, P; Seitz, H; Elliott, T; Niu, Y (2007)
We have modelled the Li budget of subducting oceanic crust during dehydration, using recently established input parameters. The results show that the entire prograde metamorphic process, up to anhydrous eclogite, can account for a decrease in δ7Li of only ≤ 3‰. Given that altered, oceanic crust entering the subduction zone should have Li isotopic compositions between - 3 and + 14‰, dehydration cannot account for markedly light Li isotopic compositions (δ7Li < 0 to - 10‰) previously measured in some high-pressure metamorphic (HPM) rocks. We have analysed another 41 orogenic HPM rocks from 11 different localities. These samples show a wide range in Li abundances from 1 to 77 μg/g. Li isotopic compositions of the rocks display both very heavy (δ7Li > + 6‰) and very light (δ7Li < 0‰) compositions, as low as - 21.9‰. Notably some of the samples with highest Li concentrations are also isotopically light, which would not be predicted by isotopic fractionation as a consequence of Li loss during dehydration. Li abundances in excess of 30 μg/g in orogenic HPM rocks of basaltic composition (eclogites) are higher than any value of altered MORB and presumably result from addition of Li after the onset of subduction, most probably during eclogitisation or exhumation. Hence we propose that light-δ7Li values are generated by kinetic fractionation of the Li isotopes during diffusive influx of Li from the country rocks into the exhuming eclogite bodies. Our conclusions are in stark contrast to the previously accepted model, as we predict the deeply subducted eclogites to have a Li isotopic signature heavier than the mantle. © 2007 Elsevier B.V. All rights reserved.